Efficacy and tolerability of a new powdered formulation of diclofenac potassium for oral solution for the acute treatment of migraine: Results from the International Migraine Pain Assessment Clinical Trial (IMPACT) - Lipton, Richard B; Grosberg, Brian; Singer, Richard P; Pearlman, Starr H; Sorrentino, James V; Quiring, John N; Saper, Joel R (Cephalalgia, 2010)
Objective: This study assessed the efficacy of diclofenac potassium for oral solution, a novel water-soluble buffered powder formulation, versus placebo for the acute treatment of migraine. Diclofenac potassium for oral solution has a time to maximum plasma concentration (Tmax) of 15 minutes, suggesting the potential for a rapid onset of therapeutic effects. Methods: This was a randomized, double-blind, parallel-group, placebo-controlled study conducted in 23 US centers. Adult sufferers with an established migraine diagnosis according to the International Classification of Headache Disorders, second edition (ICHD-II), treated one moderate or severe attack with 50 mg diclofenac potassium for oral solution (dissolved in approximately 2 ounces of water; N = 343) or matching placebo (N = 347). Four co-primary endpoints included the percentage of subjects who at two hours post-treatment reported no headache pain, no nausea, no photophobia and/or no phonophobia. Results: Significantly more subjects treated with diclofenac potassium for oral solution (N = 343) achieved a two-hour pain-free response (25% vs. 10%, p < .001), no nausea (65% vs. 53%; p = .002), no photophobia (41% vs. 27%; p < .001) and no phonophobia (44% vs. 27%; p < .001) compared to placebo. Pain intensity differences between treatments were significantly lower in the diclofenac potassium oral solution group, starting at 30 minutes post-treatment (p = .013) with significant differences at all time points thereafter (p < .001). Twenty-four-hour sustained pain-free response favored diclofenac potassium oral solution treatment versus placebo (19% vs. 7%, p < .0001). The most common adverse event considered to be treatment related was nausea (diclofenac potassium for oral solution [4.6%]; placebo [4.3%]). Conclusions: This study shows that this formulation of diclofenac potassium for oral solution is effective in reducing pain intensity within 30 minutes, which may be related to the 15-minute Tmax associated with this formulation. The rapid-onset benefits were sustained through 24 hours post-treatment.